Biochemical and hematological profiles of Gallus gallus domesticus under extensive and confinement rearing systems in tropic conditions - Daniel Paredes López (2019)
The local breed hens preserves an important genetic pool related with rusticity, diseases resistance and adaptation to the environment these characteristics contributes to make this poultry breed in a protein source for people of rural an urban sectores and instead few research are carried out in this breed for improve its production.The objective of this research was to characterize the hematological and biochemical serie profile of Gallus gallus domesticus in relationship with genetic and breeding system. For this purpose, 20 broilers Cobb-500 forty two days old, 2 kg weight, bred in confinement system and 20 local breed hens 8-10 months old, 2 kg weight., bred in extensive system were used. Entire blood and serum samples from the 40 specimens were collected. Hematocrit was determined by microhematocrit in a Hettich EBA 20 centrifuge, Hb; AST, ALT, total protein, albumin, total cholesterol and Cholesterol HDL were determined by a spectrophotometer Boeco (Germany) S-22 UV/visible and Winner Lab Kits. Hematocrit and albumin profiles in broilers Cobb-500 and local breed hens were similar (p>0.05), however, Hb, total protein, AST, ALT, total cholesterol and cholesterol HDL profiles were different (p<0.0 1), showing that total protein was higher in local breed hens than in Cob-500 breed and Hb, AST, ALT, total cholesterol and cholesterol HDL were higher in Cob - 500 broilers than in local breed hens. The genetic and confinement system influenced the increase of Hb, AST, ALT, total cholesterol and cholesterol HDL.